FPGA-based dual-layer authentication scheme utilizing AES and ECC for unmanned aerial vehicles - Kumar Sekhar Roy; Murikipudi Sujith; Bandi Bhanu; Preethi; Ruhul Amin Hazarika (EURASIP Journal on Wireless Communications and Networking)
Abstract Unmanned aerial vehicles, commonly known as drones, face unique authentication challenges due to their distinct characteristics and operational environments. These challenges include identity management, secure key management, secure communication channels, and limited resources. To address these challenges, we propose a dual-layer authentication scheme utilizing Advanced Encryption Standard and Elliptic Curve Cryptography on Field-Programmable Gate Arrays. This scheme leverages the flexibility and programmability of Field-Programmable Gate Arrays incorporated in drones to enhance security. The integration of Advanced Encryption Standard on Field-Programmable Gate Arrays provides a robust solution to withstand various attacks such as impersonation, tampering, and replay attacks. Simulation results in Xilinx Vivado demonstrate the efficiency and effectiveness of the proposed scheme compared to existing methods.